Comparison of Mean Platelet Volume (MPV) in Patients with Psoriasis and Healthy Individuals - Komal Shehzade; Saulat Zahra; Rabia Ishfaq; Kayinat Samreen; Maria Khalid; Fahad Usman (Pakistan Journal of Medicine and Dentistry)
Background: Psoriasis is a chronic inflammatory skin condition affecting quality of life, with evidence suggesting a role for platelets in its pathogenesis. Mean Platelet Volume (MPV), a marker of platelet activation, may serve as a biomarker for systemic inflammation. This study aimed to compare MPV levels between psoriasis patients and healthy controls to assess its clinical utility.